ANALISIS KINERJA PRODUKSI, NILAI TAMBAH DAN KEUNTUNGAN AGROINDUSTRI KERIPIK (STUDI KASUS AGROINDUSTRI KERIPIK BUDE DI KABUPATEN LAMPUNG UTARA) - Nirmala Devi; Dwi Haryono; Yuliana Saleh (Lampung University, 2022)
The aims of this research are to analyze the production performance, added value, and profit of chips agroindustry. Respondents were the owner and employees of agroindustry. The method used was a case study at Keripik Bude Agroindustry in North Lampung District. The study uses primary data from interviews and direct observations, as well as secondary data quoted from government agencies. The analytical methods used are analysis of production performance, analysis of added value and profit. Production performance of the chips agroindustry which includes productivity, capacity, quality, flexibility, and process rapidity overall have been maximized. The added value of processing cassava chips has a positive value of IDR12,477.07/kg of cassava raw materials and the added value of processing banana chips is IDR8,154.87/kg of banana raw materials, so the business run by the agroindustry is profitable. The total profit from selling cassava chips and banana chips is IDR514,562.50 per production or IDR5,145,625.00 per month, so this business is profitable. Key words: added value, production performance, profit